Worry about online fraud and older adults: Avoidant and protective responses - Kemp, Steven (Journal of criminology, 2025)
Given that cyber-enabled fraud makes up the vast majority of digital crime suffered by older adults, the impact of victimisation on this demographic group is of academic and practical relevance. This article examines the relationship between cyber fraud victimisation, worry about cyber fraud, and online avoidant behaviours and protective responses in older adults. The data come from the 2019 Special Eurobarometer 499, and the sample is made up of 6,257 Internet users aged 60 years and above. In addition to suffering cyber-enabled fraud, we also analyse various factors, such as the respondent's sex and knowledge of risks, which have been found to be associated with fear or worry about crime in other contexts. Our findings show that the respondent's sex and having experienced prior victimisation of oneself or family and friends is related to greater worry about online fraud. Moreover, we find that fraud victimisation of friends and family, knowledge of risks, and perceived self-efficacy are associated with dysfunctional avoidant behaviours and the adoption of functional security measures. We discuss the results in relation to gendered fear of crime socialisation and in terms of interventions with older adults that aim to respond to victimisation and to combat the digital divide.